Contact angle and surface free energy of electron-beam irradiated polymer composites - Żenkiewicz, M.; Rytlewski, P.; Czupryńska, J.; Polański, J.; Karasiewicz, T.; Engelgard, W. (Polimery, 2022)
The effects of the electron radiation dose and of compatibilizers on the contact angle and surface free energy (SFE) of the composites made of low-density polyethylene (PE-LD), high-density polyethylene (PE-HD), polypropylene (PP), polystyrene (PS), and polyethylene terephthalate (PET) were studied. Use of the high-energy electron radiation with doses up to 300kGy and of compatibilizers was done to reach better mechanical and adhesion properties of the composites studied and, at the same time, to investigate the possibility of applying of this technique in the processes of polymeric materials recycling. The compatibilizers were the styrene-ethylene/butylene-styrene elastomer grafted with maleic anhydride (SEBS-g-MA), added at the amounts of 5, 10 or 15 wt. %, and trimethylol propane trimethylacrylate (TMPTA), added at the amounts of 1, 2 or 3 wt. %. The effects, discussed in the present article, are: enhancement of wettability and increase in SFE of the composites studied. It was found that the contact angle steadily decreased and SFE of the composites increased with the rising dose of the electron radiation and that TMPTA intensified these tendencies.